Qualitative Data Collection Tool to Document Impact of Mixed Farming Systems - Sadaf, Bushra Humaira; Haque, Abdul; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2024)
The International Rice Research Institute (IRRI) has implemented the CGIAR research initiative on Mixed Farming Systems (MFS) (https://www.cgiar.org/initiative/mixed-farming-systems/) in Bangladesh since 2023. Throughout this period, farmers in five districts across northern and southern Bangladesh have been supported with various agricultural technologies under the MFS initiative.